Religion og forståelse - Bilde, Per (Religionsvidenskabeligt Tidsskrift, 2002)
The essay represents the author’s inaugural lecture held on 7 December 2001 as a professor at the Department of the Study of Religion. The essay is partly a summary of the author’s recently published monograph En religion bliver til, partly an elaboration of one of the main theses of the book. The development of early Christianity is closely related to a need for interpretation. Looking at 1 Cor 1:18-25; Rom 11:25-27; Matt 13:9-17; Mark 8:14-12 and Luke 24:13-32 Bilde attempts to find tracks in the early Jesus-texts that indicate the efforts of the Jesus-movement to understand and interpret Jesus, his message, fate and importance.